วงปี่ชวากลองแขกประกอบการชกมวยในจังหวัดชลบุรี - สุภาพร มาสมบูรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
This research aims to study the developmental history and characteristic of the Pi Java Klongkak ensemble accompanies boxing in Chonburi province, adaptation of the musicians in Pi Java Klongkak ensemble for survival. At the moment, found that Pi Java Klongkak ensemble accompanies Thai boxing in Chonburi has played both temporary boxing ring and standards boxing stadium. Musician in the band does not found clearly appearance line of transition. Most of the musicians are in a band as Piphat ensemble, including the Pi musician who almost learn on their own and inherit each other s knowledge. The band are mixed by combining the band of musicians from various bands. The Pi Java Klongkak ensemble accompanies Thai boxing in Chonburi are hiring to perform in a temporary boxing ring is Charoensilp. The standards boxing stadium include Fairtex Thepprasit Boxing Stadium, South Pattaya and North Pattaya Boxing Stadium in front of Minisiam (Pattaya Boxing World), a band which played regularly is Charansilp. The income and promotion problems in the boxing business, which raised more boxing match that affect Pi Java Klongkak ensemble to survive, a number of instruments, musicians and songs are adapted. The instruments in the ensemble originally consisted by each one instrument: Pi Java, Ching and pair of Klongkak but only play one separated drum by one drummer. The playing of accompanied boxing songs, even maintaining the origin tradition include playing Sarama accompanied Wai Kru in the round 1, Khak Jowsen in round 5, Cherd within one minute before the time over, but play the independence songs with round 2 to round 5 based on the intelligence of the musicians in adapting the popular song to please the audience. The music perform will be stopped if the boxer could not continue the fighting in any round.